Tractations et accommodements - Gallon, Florian (CPIM, 2023)
In the Middle Ages, the Iberian Peninsula and the Maghreb constituted a frontier zone where Christianity and Islam lived side by side and met, ignored each other and interacted, clashed and agreed. In addition to their own distinctive characteristics, the Christian and Muslim worlds were themselves largely composite entities. Political fragmentation, social heterogeneity and denominational plurality multiply the opportunities and reasons for tension and discord. These dissensions sometimes lead to confrontation, but can also be resolved or smoothed out by the search for common ground and compromise. It is these negotiations and accommodations, in all their variety, that are the focus of this dossier. Over a long period of time and across a vast geographical area considered on a variety of scales, the contributions brought together here aim to provide a better understanding of the modalities and functions of these negotiations and conciliations in the search for middle ground, in the diplomatic, political or economic spheres, while highlighting the difficulties and resistance that hinder their development or limit their effectiveness.